PEMAJUAN OBJEK KEBUDAYAAN BAHASA JAWA MELALUI PEMBELAJARAN KREATIF SI BATARA JAWA - Setyawan, Agung Vendi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
Javanese is a native language, a regional language, and a cultural object that serves as a medium of communication. It is essential to protect Javanese as a world cultural heritage by passing it on and fighting for this cultural object. Sinau Basa, Sastra, lan Aksara Jawa (Si Batara Jawa) is a creative local content learning program in Javanese language as a tangible manifestation of the promotion of cultural objects, especially the Javanese language. Si Batara Jawa's creative learning activities include making vlogs in Javanese; learning Javanese literature through the creation of geguritan (Javanese poetry) integrated with the use of the Canva application; learning Macapat Pocung literature integrated with mathematics; and learning Javanese script using a step-by-step technique integrated with art lessons. Si Batara Jawa can improve students' understanding of teaching materials and motivate them to learn, love, and develop their creativity. The implementation of Si Batara Jawa using digital technology can guide students to be smart and creative in learning Javanese language, literature, and script teaching materials so that they can preserve and advance Javanese language culture.